La villa gallo-romaine de Grigy à Metz (ier s. apr. J.-C.-ve s. apr. J.-C.) : caractérisation fonctionnelle des structures et identification des activités artisanales - Gaël Brkojewitsch; Sandrine Marquié; Geneviève Daoulas; Guilherme Remor de Oliveira; Gaëtan Jouanin; Nicolas Garnier; Michaël Brunet; Simon Sedlbauer; Willy Tegel; Nadia Cantin; Valérie Thirion-Merle (Gallia)
In 2011, an archaeology investigation enabled the identification of a whole Gallo-Roman villa, its outbuildings and its linked facilities during the extension of a commercial activity zone, to the south-east of Metz, in the Grigy area. This paper briefly describes the geographical and archaeological situation, and introduces the general organization of the site. Then, the archaeological description of the buildings is divided into three parts, following chronological considerations : the overview of the Protohistoric buildings, of a funerary early Gallo-Roman structure and finally, the remains of the villa, in two subsections regarding the pars urbana and the pars rustica. The very well preserved amenities found in the pars rustica courtyard – three wooden tanks and a basin with a wooden floor – suggest some craft activities. We finally focus on the identification of this/these activity/ties with the help of different studies (lead objects, plant macro-remains) and analysis (organic chemistry, mineralogical analysis) to look into several hypothesis: leather, wood or fiber exploitation (tannery, basketry, fabric work). Our interpretation leads to the soaking and retting of plant-fibres. The last part of the paper focuses on the successive chronological phases, taking into account the results of the pottery’s study, on the basis of absolute datings (radiometry, dendrochronology). The occupation is thus divided into four stages, suggesting that the villa was founded in the last quarter of the 1st c. B.C., then dismantled and deserted between the end of the 4th c. and the start of the 5th c. A.D.